Thinner bark increases sensitivity of wetter Amazonian tropical forests to fire - Staver, Ann Carla; Brando, Paulo M.; Barlow, Jos; Morton, Douglas C.; Paine, C.E. Timothy; Malhi, Yadvinder; Araujo Murakami, Alejandro; Pasquel, Jhon (Dryad, 2019)
Understory fires represent an accelerating threat to Amazonian tropical
forests and can, during drought, affect larger areas than deforestation
itself. These fires kill trees at rates varying from < 10
to c. 90% depending on fire intensity, forest disturbance history and tree
functional traits. Here, we examine variation in bark thickness across the
Amazon. Bark can protect trees from fires, but it is often assumed to be
consistently thin across tropical forests. Here, we show that investment
in bark varies, with thicker bark in dry forests and thinner in wetter
forests. We also show that thinner bark translated into higher fire‐driven
tree mortality in wetter forests, with between 0.67 and 5.86 gigatonnes
CO2 lost in Amazon understory fires between 2001 and 2010.
Trait‐enabled global vegetation models that explicitly include variation
in bark thickness are likely to improve the predictions of fire effects on
carbon cycling in tropical forests.
Keywords: Carbon cycle; Amazonia